Mortality of young Nicaraguan inmigrants in Costa Rica during the 2000-2017 period - Bonilla-Carrión, Roger E. (Universidad y Salud, 2021)
Introduction: Poverty, discrimination, and social isolation are some elements that affect Nicaraguan immigrants residing in Costa Rica, conditions that have an impact on the mortality figures observed in this migrant population. Objective: To determine mortality rates caused by diseases and external reasons in both the young Nicaraguan immigrant population and native Costa Rican natives. Materials and methods: Data on deaths between 2000 and 2017 and the 2011 Census information of the Costa Rican population were used to calculate mortality rates and the relative risk (RR) associated with different causes of mortality. Results were compared to a study that analyzed this phenomenon between 1998-2008. Results: Compared to the deaths in the Costa Rican population (57%), 64% of deaths in immigrants are due to external causes. With respect to the data from 10 years ago, there is a 2-percentage point reduction in deaths of immigrants caused by external reasons. Immigrants show higher RRs of mortality due to external causes (other accidents 1.85, homicides 1.72, car accidents 1.22, and suicide 1.14). A reduction of 2.27 and 0.15 in the RR of homicides and alcoholism, respectively, is highlighted. Conclusions: Mortality patterns in immigrants begin to behave as those of the Costa Rican population.